Strategy and Tactics: Chinese Immigrants and Diasporic Spaces in Johannesburg, South Africa - Harrison, Phillip. Moyo, Khangelani. Yang, Yan (Journal of Southern African Studies, 2012)
Migration studies in South Africa have partially taken the spatial turn, giving some attention to questions of territoriality and spatial relationships. Recent literature has drawn on de Certeau’s distinction between the strategies of the powerful and the tactics of the subordinate, revealing for example how migrants occupy hidden spaces to evade control and social hostility. Within the broad aegis of de Certeau’s work, we engage the historical and contemporary spaces of the Chinese diaspora in Johannesburg. We describe a highly differentiated grouping of migrants that has deployed, and continues to deploy, varying tactics over time and across space. There are, for example, processes of clustering and processes of dispersal. There is also the use of visibility and cultural marking as a spatial tactic, as well as of invisibility and hidden spaces. We also reveal that the spatial practices of the Chinese migrants do not only relate to the strategies of the powerful but are also a response to the competition and threats posed by other subordinate individuals and groupings in society, including other Chinese migrants.
Keywords: Migration || Chinese Migrants || Migrand grouping